2023
DOI: 10.23876/j.krcp.22.118
|View full text |Cite
|
Sign up to set email alerts
|

Pleotropic effects of hypoxia-inducible factor-prolyl hydroxylase domain inhibitors: are they clinically relevant?

Abstract: Anemia is common in patients with chronic kidney disease (CKD) and is mainly caused by insufficient production of erythropoietin from fibrotic kidney. Because anemia impairs quality of life and overall prognosis, recombinant human erythropoietin-related products (erythropoiesis-stimulating agents, ESAs) have been developed to increase hemoglobin level for decades. However, many safety concerns have been announced regarding the use of ESAs, including an increased occurrence of cardiovascular events, vascular ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…It is generally considered an essential process for adaptive responses to hypoxia. 76 Recently, Li, et al 77 revealed that under hypoxia, HIF-1a can bind to Forkhead box O3 (FoxO3), a stress-responsive transcription factor known to upregulate autophagy after UUO, subsequently suppressing prolyl hydroxylation and degradation of FoxO3 by the ubiquitin-proteasome system. The removal of FoxO3 from tubular cells can lead to increased interstitial fibrosis after ischemia-reperfusion Injury, with a decrease in autophagy and more severe oxidative damage.…”
Section: Aki-to-ckd Transition: Recent Mechanistic Insightsmentioning
confidence: 99%
“…It is generally considered an essential process for adaptive responses to hypoxia. 76 Recently, Li, et al 77 revealed that under hypoxia, HIF-1a can bind to Forkhead box O3 (FoxO3), a stress-responsive transcription factor known to upregulate autophagy after UUO, subsequently suppressing prolyl hydroxylation and degradation of FoxO3 by the ubiquitin-proteasome system. The removal of FoxO3 from tubular cells can lead to increased interstitial fibrosis after ischemia-reperfusion Injury, with a decrease in autophagy and more severe oxidative damage.…”
Section: Aki-to-ckd Transition: Recent Mechanistic Insightsmentioning
confidence: 99%
“…PHD inhibitors may have different effects on PHD isoforms, which may cause variations in HIF levels and, thus, pleiotropic effects. Further research is needed to elucidate how they can be used in human diseases [117]. Nowadays, there are numerous advancements and potential applications regarding the possibility of modulating HIFs to exert positive effects.…”
Section: Hints Of Potential Therapeutic Strategiesmentioning
confidence: 99%
“…This could allow for early intervention and the implementation of preventative measures to minimize the occurrence and severity of intimal hyperplasia. 14 The mechanism through which umbilical cord mesenchymal stem cells exert their anti-intimal hyperplasia effects is multi-faceted. Firstly, these stem cells have the ability to differentiate into various cell types involved in vascular remodeling and repair.…”
Section: Level Of Hif-1αmentioning
confidence: 99%